Identifikasi Kandungan Logam Berat Menggunakan Metode X-Ray Fluorescence (XRF) Pada Sedimen Sungai Citarum Bagian Hulu - Hilmi Liesdiawan, Naufal; Pharmawati, Kancitra; Rizka Maria (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Citarum River, the largest and longest river in West Java Province, is heavily polluted due to human activities such as domestic, agricultural, and industrial. This condition causes heavy metal pollution that endangers the ecosystem around the waters. This study aims to identify the level of dissolved heavy metal contamination in the upstream Citarum River, particularly in Bandung Regency, using the X-Ray Fluorescence (XRF) method, an analytical technique used to identify chemical elements in a sample by measuring the X-rays emitted after the sample is excited by primary X-rays. The test results show the concentration of heavy metals in the sediments of the upstream Citarum River, namely Fe between 67,924.8 - 47,584 ppm, Mn 406.1 - 2,107.1 ppm, Cu 54.5 - 59.7 ppm, Pb 18.8 - 22 ppm, Cr 24.4 - 29.1 ppm, and Cd 17.7 - 20.4 ppm. Sediment treatment is required when heavy metal concentrations exceed the established quality standards, especially in reducing heavy metals in industrial activity wastewater. In the deconstruction process for cadmium analysis, it is necessary to pay attention to the amount of HCL reagent solution used, because cadmium is easily dissolved by HCL. Excessive dosage can reduce or eliminate the concentration of cadmium in the sample. This research highlights the need for better waste management to maintain the water quality of the Citarum River.